PEMANFAATAN VIRTUAL REALITY PADA PERANCANGAN GAME FRUIT SLASH BERBASIS ANDROID MENGGUNAKAN UNITY 3D - Rangga Septyan Putra; Dwi Yuni Utami (Universitas Bina Sarana Informatika, 2018)
Nowadays games become one of the choices of activities to fill in leisure time or just to amuse themselves during leisure time, because the game is made with a fun and entertaining game system. The current games are very diverse, such as games with puzzles, games that require dexterity to games that require concentration. However, most existing games still use touch screen or touchscreen media, so some games that require fast reflexes from players will cause difficulties. In this study aims to create a fruit slash entertainment media where players can cut fruit as if real. The game fruit slash app is a game designed by applying Virtual Reality technology that will simplify and maximize excitement while playing the game. Game Fruit Slash is also made by using the engine (game programming) Unity 3D using C # programming language. Game Fruit Slash can be played on android based mobile devices. Expected with the game fruit slash players will be able to feel the new experience. The first test using white box method is a method that uses procedural control control structure to obtain test case. The second test uses the black box method to ensure that an event or input will execute the appropriate process and generate output according to the design. The third test was conducted on fruit slash game application quality test by distributing questionnaires to fruit slash players. And the results of questionnaire data processing is 3.8 (strongly agree) on the aspects of benefits.